Laparoscopic Treatment of an Incarcerated Meckel’s Diverticulum in a Femoral Hernia - Christoph Paasch; Gianluca De Santo; Peter Look; Katherina Boettge; Michael Hünerbein (Case Reports in Surgery)
Meckel’s diverticulum (MD) is the persistence of the omphalomesenteric duct. It is usually asymptomatic but may present with bleeding, infections, and intestinal obstruction. It also may be a content of a hernia sac, a so-called Littre hernia. Herein, we will present the case of a 75-year-old female, who suffered from a painful swelling of the right inguinal region. Ultrasound imaging detected an inguinal hernia with incarcerated blind ending small bowel. Immediately, a laparoscopy was conducted. We diagnosed a right femoral hernia with an incarcerated MD. A TAPP (transabdominal preperitoneal) procedure was performed and the MD tangential stapled. Due to an uneventful postoperative course, the patient left the hospital after two days. An incarceration of a MD in a femoral hernia is rare. Tangential resection of the MD with simultaneous hernia repair in a TAPP technique seems to be a sufficient approach, when it is conducted by an experienced surgeon.